(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Current article provides an overview of current water purification, filtration methods, & technologies. water purification is primarily addressed for a sensitive reason: it is one of most important sources of survival for all living things. water may be found in various forms on earth’s surface, & lakes & rivers provide a significant quantity of drinking water. all living things need water to survive, but humans require filtered water that is high in minerals & salts. lack of germs & disease causing microbes, dissolved metal ions, & heavy contaminants is referred to as pure water. drinking water must be not only pure but also healthful in order to be fully functional. some water purification methods use hazardous polymers & terrible chemical compositions. n-current methods for water purification & filtration were upgraded & incorporated into nanotechnology & polymers. reverse osmosis is foundation for any purification process that employs semipermeable membranes with ultra, micro, & nano porous membranes to remove germs, microorganisms, minerals, & salts. if consumed over an extended period of time, this ro-processed water may cause sickness. to overcome need to add minerals & salts to water, fiber composites & mineral cartridges were developed. all of se water purification methods, as well as use of fiber composites & polymer membranes, are discussed in this article, along with flaws that may do a lot of harm to humanity.